2021
DOI: 10.1186/s13098-020-00622-3
|View full text |Cite
|
Sign up to set email alerts
|

Overall reduced lymphocyte especially T and B subsets closely related to the poor prognosis and the disease severity in severe patients with COVID-19 and diabetes mellitus

Abstract: Background A dysregulated host immune response is common in patients with COVID-19. Aim In this study, we aimed to define the characteristics of lymphocyte subsets and their relationship with disease progression in COVID-19 patients with or without diabetes mellitus (DM). Methods The baseline peripheral lymphocyte subsets were compared between 55 healthy controls and 95 patients with confirmed COVID-19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…A decrease in both CD4+ and CD8+ T cells is reported in COVID-19 patients with different disease severities, which is more significant in severe and critical patients [43] , [45] , [51] , [52] , [54] , [57] , [58] , [60] . Histological analysis of deceased COVID-19 patients showed that the CD4+ and CD8+ T cells decreased in the spleen and lymph nodes of these patients [68] .…”
Section: Lymphocytesmentioning
confidence: 90%
See 2 more Smart Citations
“…A decrease in both CD4+ and CD8+ T cells is reported in COVID-19 patients with different disease severities, which is more significant in severe and critical patients [43] , [45] , [51] , [52] , [54] , [57] , [58] , [60] . Histological analysis of deceased COVID-19 patients showed that the CD4+ and CD8+ T cells decreased in the spleen and lymph nodes of these patients [68] .…”
Section: Lymphocytesmentioning
confidence: 90%
“…Lymphopenia following SARS-CoV-2 infection has been reported in many studies [43] , [44] , [45] , [46] , [47] , [48] , [49] . About 85% of patients who need to be hospitalized have lymphopenia [45] , [50] with a decrease in both T and B lymphocytes [44] , [45] , [51] , [52] , [53] , [54] . However, a study noted that the lymphocyte count remained in the normal range in mild COVID-19 patients [55] .…”
Section: Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations indicate that immune system dysfunction or dysregulated host immune response is commonly noted in individuals affected with COVID-19. The authors concluded that the immune-modulatory treatment should be considered to reduce disease progression and prognosis of COVID-19 patients, especially in patients with systemic co-morbidities [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our clinical data have revealed that increased NEU, decreased LYM, MONO, EOS, MPV, PCT, BASO, and INR levels in the deceased dementia patients infected by COVID-19 compared to the survived ones (Figure 6). Indicated changes in the blood biomarkers are tightly associated with a higher risk of mortality and disease progression [31]. Also with aging, leukocytosis, lymphocytopenia, neutrophilia, anemia, and severe in ammatory state were observed that are overlap with the COVID-19 pathology which may severe symptoms in the elderly patients [17].…”
Section: Discussionmentioning
confidence: 99%